Blunt laryngeal Trauma In Sudanese Agricultural Workers:Two case reports - El Mustafa, Osman Mohamed (Gezira Journal of Health Sciences, 2003)
In this article two cases of blunt laryngeal trauma are reported in Sudanese agricultural workers. The clinical presentation and the mechanism of injuries are discussed. The main cause of injury in both cases was trapping of loose clothing in agricultural machinery with a fatal outcome in one of them. Avoidance of loose clothing and wearing of more tight ones (overalls) are advised to avoid somewhat rare but serious injuries.